Design and Implementation of IOT Based Smart Healthcare Systems for Rural Area People - Dr. T. Vasudeva Reddy, G. Maniratnam, B. S. Devaraj, B. James, R. Prapul Kumar (Design Engineering, 2021)
In hospitals when a patient is in ICU, it is very important to monitor physiological signals of the patient. Pulse rate, temperature, Humidity etc are highly important signals included in the physiological signals. It is very difficult work for doctors to monitor each patient all the time. The research is based on embedded hardware module(MSP430G2553)aultra-low power microcontroller from Texas Instruments. The sensors are temperature and humidity, pulse, with the help of these the physiological signals of the patient are taken and displays the data on a LCD and also transfers to the cloud using Node MCU a WIFI module and can be accessed by devices which has internet access. So doctor or personal staff can easily analyze patient’s status can be visualized by doctor  from personal computer, smart phone, tablet etc.